2013
DOI: 10.1007/s12010-013-0532-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Operating Conditions in Production of Diagnostic Salmonella Enteritidis O-Antigen-Specific Monoclonal Antibody in Different Bioreactor Systems

Abstract: In this study, different cultivation systems such as roller bottles (RB), 5-L stirred-tank bioreactor (STR), and disposable bioreactors were used to cultivate hybridoma for lab-scale production of Salmonella Enteritidis O-antigen-specific monoclonal antibody (MAb). Hybridoma cell line was cultivated in either serum-containing or serum-free medium (SFM) culture conditions. In STR, MAb production scaled up to 4 L, and production capabilities of the cells were also evaluated in different featured production syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The roller bottles, stirred tank and disposable bioreactors have been operated with both serum and serum-free media. It was found that the cells were not able to adapt to serum-free media in roller bottles and stirred tank bioreactors [ 12 ]. The highest monoclonal antibody titre was observed in a disposable static membrane bioreactor and the peak productivity was found in a stirred tank bioreactor operated in semicontinuous mode with overlay aeration [ 12 ].…”
Section: Track To the Emergence Of High-density Cell Culture Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The roller bottles, stirred tank and disposable bioreactors have been operated with both serum and serum-free media. It was found that the cells were not able to adapt to serum-free media in roller bottles and stirred tank bioreactors [ 12 ]. The highest monoclonal antibody titre was observed in a disposable static membrane bioreactor and the peak productivity was found in a stirred tank bioreactor operated in semicontinuous mode with overlay aeration [ 12 ].…”
Section: Track To the Emergence Of High-density Cell Culture Systemsmentioning
confidence: 99%
“…It was found that the cells were not able to adapt to serum-free media in roller bottles and stirred tank bioreactors [ 12 ]. The highest monoclonal antibody titre was observed in a disposable static membrane bioreactor and the peak productivity was found in a stirred tank bioreactor operated in semicontinuous mode with overlay aeration [ 12 ]. Serum free medium has also been successfully used in high cell density bioreactors such as hollow fiber systems [ 18 ], packed bed reactors [ 19 ] and wave bioreactors [ 20 ] for the cultivation of mammalian cells.…”
Section: Track To the Emergence Of High-density Cell Culture Systemsmentioning
confidence: 99%
“…However, because of ethical concerns and because antibodies have to meet strict quality control requirements (purity, similarity, identity) the number of animals used for antibody production for diagnostic and scientific purposes is continuously decreasing. In parallel, in recent years, numerous bioreactors have been developed for cultivation of hybridoma cells and several types of in vitro antibody production methods were established (Nagel et al 1999;Trebak et al 1999;Ayyildiz-Tamis et al 2014). …”
Section: Introductionmentioning
confidence: 99%